2021
DOI: 10.1155/2021/5585077
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Aerobic Exercise Training along with Oak Husk Hydroalcoholic Extract for Amelioration of Inflammation in Obese Elderly Male Mice

Abstract: Background. Fibrinogen and interleukin-1β as a proinflammatory cytokine and interleukin-10 and nesfatin-1 as an anti-inflammatory cytokine have an important role in the development and prevention of systemic inflammation and incidence of obesity-induced diseases. Thus, this study is aimed at the interaction effects of aerobic training and oak husk hydroalcoholic extract consumption on plasma levels of fibrinogen, interleukin-1β, nesfatin-1, and interleukin-10 in obese elderly male mice. Materials and Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The training groups performed aerobic exercise 5 days a week for 6 weeks (approximately 80%–75%). The results showed that 6‐week training significantly increased the concentration of Nesfatin‐1 in the experimental group 68 …”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The training groups performed aerobic exercise 5 days a week for 6 weeks (approximately 80%–75%). The results showed that 6‐week training significantly increased the concentration of Nesfatin‐1 in the experimental group 68 …”
Section: Resultsmentioning
confidence: 92%
“…From the 36 included studies, 23 examined humans 41–63 with 13 examining animal models 64–76 . Studies investigated the effects of chronic exercise training 41–51,63 and acute exercise 48,52–62 in humans.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations